Some considerations to optimize the synthesis procedure and the structural quality of mesostructured silicas - Elías, Verónica Rita (2009)
Two methods for the preparation of highly ordered MCM-41 silica are discussed. The quality of the structure was optimized by adequate stirring of the reaction mixture containing low concentration of surfactant, followed by heating at 70 °C for 3 h under stirring. Besides this energetically favorable procedure allowed to obtain structures very stable upon calcination. The role of the ethanol and the hydroxide source in the synthesis process is also analyzed.